2017
DOI: 10.3892/or.2017.5395
|View full text |Cite
|
Sign up to set email alerts
|

Calcium release induced by 2-pyridinecarboxaldehyde thiosemicarbazone and its copper complex contributes to tumor cell death

Abstract: Thiosemicarbazones display significant antitumor activity and their copper complexes also exhibit enhanced biological activities in most situations, but the underlying mechanism is poorly understood. Therefore, investigation of the mechanism involved in the change upon chelation is required to extend our understanding of the effects of thiosemicarbazones. In the present study, the inhibitory effect of 2-pyridinecarboxaldehyde thiosemicarbazone (PCT) and its copper complex (PCT-Cu) on cell proliferation was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
0
11
0
1
Order By: Relevance
“…Next, the ferric would be reduced by the reducing agents, which triggered Fenton reaction, producing massive ROS that caused an alteration in LMP. To test the hypothesis, LysoTracker Red that can accumulate within lysosomes was employed to assess the lysosome membrane permeability [ 13 ]. As shown in Figure 8 , the red fluorescence intensities of HepG2 cells were increased with treatment of DpdtC compared to nontreatment of the cells, indicating that more LysoTracker Red accumulated in lysosomes and LMP was altered ( Figure 8(b) ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the ferric would be reduced by the reducing agents, which triggered Fenton reaction, producing massive ROS that caused an alteration in LMP. To test the hypothesis, LysoTracker Red that can accumulate within lysosomes was employed to assess the lysosome membrane permeability [ 13 ]. As shown in Figure 8 , the red fluorescence intensities of HepG2 cells were increased with treatment of DpdtC compared to nontreatment of the cells, indicating that more LysoTracker Red accumulated in lysosomes and LMP was altered ( Figure 8(b) ).…”
Section: Resultsmentioning
confidence: 99%
“…A cancer cell has higher iron demand than normal cell; reduction of iron availability will be a favor to inhibit cancer cell proliferation. One of the mechanisms of iron chelators is a disturbance of iron homeostasis [ 13 17 ], in addition, iron chelators can also induce apoptosis, autophagy, and inactivate ribonucleotide reductase. Therefore, iron chelation has been considered as a promising strategy in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Metal chelators are promising therapeutic agents that show marked and selective anti-tumor activity 1 , 2 . As we know, cancer cells have an increased demand for iron and copper to maintain proper cell growth rate; therefore, the use of chelators for cancer treatment has been an potential option 3 , 4 . The iron chelators such as di-2-pyridyl ketone-4,4-dimethyl-3-thiosemicarbazone (Dp44mT) and desferrioxamine (DFO) have shown pronounced inhibitory effects in several types of cancer 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…NDRG1 belongs to the NDRG (N-myc downstream-regulated gene) family which has been reported to function as a tumor and metastasis suppressor gene in several types of cancer including breast, pancreatic and prostate cancers 9 – 12 . Studies have shown that iron and copper chelators exhibited their anti-tumor effects through up-regulating NDRG1 level to regress tumor growth and suppress metastasis 4 , 13 , 14 . Moreover, chelators such as those of the dipyridyl thiosemicarbazone (DpT) class also exerted their metastasis-suppressive effects through up-regulating NDRG1 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Este composto também apresenta uma grande habilidade em se coordenar com vários íons metálicos de interesse biológico através dos átomos de nitrogênio piridínico, nitrogênio azometínico e oxigênio carbonílico. A 2-piridinacarboxaldeído, um dos precursores do 2PCAFUR, é reportada na literatura possuindo atividade anticâncer (Qi et al, 2017), antitumoral (Fu et al, 2017), antibacteriana, catalítica e ainda é empregada como material fotoativo (Ali et al, 2015). Além disso, a hidrazona formada a partir deste precursor atua como agente quelante em doenças relacionadas ao excesso de ferro (Richardson e Ponka, 1998;Richardson et al, 1999;Richardson, 2003;Richardson et al, 2006).…”
Section: Pcafur: 2-piridinacarboxaldeído Furoil Hidrazonaunclassified